Paths of Evolution of Territorial Identity. The Case of Former Towns in the Katowice Conurbation - Mihaylov, Valentin; Runge, Jerzy; Krzysztofik, Robert; Spórna, Tomasz (Geographica Pannonica, 2019)
In this study we focus on the evolution of the identity of those urban neighbourhoods which have formerly been separate towns. This problem is discussed using the example of the polycentric conurbation of Katowice in southern Poland, which came into being because of its mining and industrial functions. The administrative integration of this multi-level polycentric urban system is the primary background for the development of those neighbourhoods that used to be separate towns. Assuming that changes in legal and administrative status may have certain consequences regarding the social connections and identity of such neighbourhoods, this study aimed to identify such places within the analysed region. The authors also attempted to construct paths of local identity for such spatial entities, confronting them with the thesis that economic factors make them relatively homogeneous. The implementation of new development factors and the paradoxical diversity of the identities of the former towns in this mining-industrial region are also significant elements of the region’s social transformation in terms of economic and spatial development.